Anti‐neurotoxic evaluation of synthetic and characterized metal complexes of thiosemicarbazone derivatives. (2nd January 2018) - El‐Saied, Fathy A.; Salem, Tarek A.; Shakdofa, Mohamad M.E.; Al‐Hakimi, Ahmed N.
Abstract : Quinoline‐2‐caboxyaldehyde thiosemicarbazone (HL 1 ) and quinoline ‐2‐caboxyaldehyde N‐dimethyl thiosemicarbazone (HL 2 ) metal complexes were prepared and characterized using analytical and spectroscopic techniques. The measurements showed that ligands behave as monovalent or neutral tridentate ligands bonding via azomethine, quinoline ring nitrogen atoms and sulfur atoms in thiol or thion forms. The anti‐neurotoxic effect of ligands and their complexes showed that, exposure to aluminum increase oxidative stress in the brain, an effect that could be offset by concomitant thiosemicarbazone complexes. Complexes could be having an effect on absorption or excretion of aluminum, due to their chelating activity. These findings may shed light on the potential clinical importance of thiosemicarbazone complexes in Alzheimer's disease. Abstract : Anti‐oxidative and chelating activity of quinoline‐2‐caboxyaldehyde thiosemicarbazone (HL 1 ) and quinoline ‐2‐caboxyaldehyde N‐dimethyl thiosemicarbazone (HL2)